Research Trends about Analogy Studies in Science Education: A Descriptive Content Analysis - Kübra Sezer; Faik Özgür Karataş (Universitas Pendidikan Indonesia, 2022)
Analogies are bridges between prior knowledge and new knowledge to make meaning of the new one. Analogies are particularly effective in teaching science concepts that are not very apparent in the students' everyday lives due to their abstract nature. For this reason, it is essential to adapt analogies to teach new concepts effectively in science education. Analogy-related studies published between 2009 and 2020 were examined in this manuscript to determine the use of analogies as a teaching technique in science education (Physics, Chemistry, Biology). To reach the studies about